Substrate Discrimination by ClpB and Hsp104 - Johnston, Danielle M.; Miot, Marika; Hoskins, Joel R.; Wickner, Sue; Doyle, Shannon M. (Frontiers in Molecular Biosciences, 2017)
ClpB of E. coli and yeast Hsp104 are homologous molecular chaperones and members of the AAA+ (ATPases Associated with various cellular Activities) superfamily of ATPases. They are required for thermotolerance and function in disaggregation and reactivation of aggregated proteins that form during severe stress conditions. ClpB and Hsp104 collaborate with the DnaK or Hsp70 chaperone system, respectively, to dissolve protein aggregates both in vivo and in vitro. In yeast, the propagation of prions depends upon Hsp104. Since protein aggregation and amyloid formation are associated with many diseases, including neurodegenerative diseases and cancer, understanding how disaggregases function is important. In this study, we have explored the innate substrate preferences of ClpB and Hsp104 in the absence of the DnaK and Hsp70 chaperone system. The results suggest that substrate specificity is determined by nucleotide binding domain-1.□